Feasibility of Biopreneurship Project-Based Science Module for Students in the Bagek Kembar Ecotourism Area - X Zardht Alex Hidayat; I Putu Artayasa; A Wahab Jufri (Jurnal Penelitian Pendidikan IPA, 2024)
The biopreneurship project-based science module is teaching material designed to combine biological concepts with entrepreneurship through project-based learning. This research aims to develop a biopreneurship-based science module valid for increasing students' scientific literacy, entrepreneurial motivation, and environmental literacy in the Bagek Kembar Ecotourism Area. This research is development research using the ADDIE model, namely Analyze, Design, Development, Implementation, and Evaluation. The development and validation stages of the module were carried out at the University of Mataram and SMA Negeri 1 Sekotong. The research instrument was a validation questionnaire given to science experts and teachers. The validity of the Science Module is based on the Aiken V Index. The results of the biopreneurship project-based science module validity show that the Aiken V Index for the size and appearance of the module cover, module design, module content, and language used are 0.95, 0.95, 0.93, and 0.94, respectively. Included in the valid category. This research concludes that the biopreneurship project-based science module is suitable for use in schools to increase students' scientific literacy, entrepreneurial motivation, and environmental literacy in Bagek Kembar ecotourism.